IMPEMENTASI KEBIJAKAN PENDIDIKAN GRATIS 9 TAHUN DI KECAMATAN DUMOGA KABUPATEN BOLAANG MONGONDOW - KARAMOY, TRISKA TAKESI; RORONG, ARIE JUNUS; KOLONDAM, HELLY (Sam Ratulangi University, 2018)
The purpose of the study was to determine the implementation of the 9 year free education policy in the Dumoga sub-district Bolaang Mongondow. This study uses a quantitative approach the research were 10 people from the school, school committees, and community parents. Data collection uses interview and observation guidalines while the analytical technique uses is the interactive analysis model from Miles and Hubernann. Based on the results of data analysis in drawing conclusions that the implementation of the 9 year free education sub-district is seen from the dimension of the idealized policy, the dimension of the target groups, of the dimension implementing organization, of the dimension environmental factors are all good but not maximum. Based on the conclusions the resuls of the study were recommended. (1) Dimension â€œIdealized Policyâ€ to be improved by building more effective communication with the community through information and counseling activities,as well asincreasing coordination relevant parties. (2) Dimension â€œTarget groupsâ€ need to bee improved by making more affective efforts and actions to increase support for the implementation of the 9 year free education policy. (3) Dimension â€œImplementing organizationâ€ need to be optimizing the role of the implementer especially the school and school commitees. (4) Demension â€œEnvironmental factorâ€ which so far has been sufficient to support cultural, social, economic and political need to be maintained and improved.Keywords : Policy Implementation, free education.PENDAHULUANKemajuan pembangunan